Renal artery clipping attenuates the progression of adriamycin nephropathy - Balbi, André Luis [UNESP]; Franco, RJS; Barretti, Pasqual [UNESP]; Gavras, I; Gavras, H. (Elsevier B.V., 1998)
This study was designed to analyze the impact of diminished renal perfusion pressure due to renal clipping on the rat model of adriamycin nephropathy. Male Wistar rats, divided into four groups (n = 9 per group) were injected with saline as control (C), adriamycin 3 ml/kg (Ad), saline with the left renal artery clipped (Rv), and adriamycin plus clip (AdRv). After 24 weeks mean arterial pressure (MAP), inulin, and p-aminohippurate (PAH) clearances were performed to evaluate renal function. Morphologic analysis included histologic criteria of percentage of glomerulosclerosis and tubulointerstitial lesion index (TILI). The MAP (mm Hg) was similar between Rv (143 +/- 13) and AdRv (154 +/- 20), but higher (P < .05) than C (120 +/- 8) and Ad (124 +/- 11). Inulin clearance (mL/min/100 g) in Ad (0.2 +/- 0.05) was smaller than in C (0.53 +/- 0.17) and Rv (0.4 +/- 0.01) (P < .05), and was at an intermediate level in AdRv (0.33 +/- 0.2). The level of PAH (mL/min/100 g) was normal at 1.76 in C, and diminished more in Ad (0.58) than in Rv (1.06) and AdRv (1.18) (P < .05). Both Ad and the AdRv nonclipped kidneys had the highest degree of glomerulosclerosis (33% and 25%) and TILI (7% and 8%), respectively, compared with C and Rv (both 0%), whereas the clipped kidneys displayed intermediate degrees (9% and 5%) (P < .05 v nonclipped). The data suggest that diminished perfusion pressure of the clipped kidney, by decreasing the intraglomerular pressure, protects the glomerulus from damage and attenuates the evolution of adriamycin nephropathy. Am J Hypertens 1998;11:1124-1128 (C) 1998 American Journal of Hypertension, Ltd.
Keywords: adriamycin; adriamycin nephropathy; renal hypoperfusion; progression of nephropathy; two-kidney-one-clip hypertension